Kinerja Perekonomian Kawasan Andalan Joglosemar Tahun 1996-2006 - Noviani, Rita (Forum Geografi, 2010)
This research of prime mover region in Joglosemar consists of 5 regencies and cities in DIY province and 16 regencies and cities in Central Java Province. Those twenty-one regencies are split into four clusters, the Jogja Cluster, Solo Cluster, Semarang Cluster and Corridor Cluster. The objective of this research is to know regional economic performance by looking at the regional division using Klassenâs typology. Main method of this research is case study, the data that was used are secondary data for 10 years in the form of the Gross Regional Domestic Product at Constant Prices 2000, Economic sectors, PDRB per capita and Population Data which was acquired from Kantor Badan Pusat Statistik (The Central Statistical Agency) and BAPPEDA (Regional Planning Board) DIY and Central Java. Data processing techniques are qualitative, descriptive and quantitative analysis. The quantitative technique is Klassenâs typology to know the performance of regional economy, and the qualitative techniques are used to know the true meaning behind the data by a deep interview. According to Klassenâs typology analysis, there are 4 spatial classes of regional economy; namely high growth and high income, high income but low growth, high growth but low income, and low growth and low income. So that the regional function as a prime mover can give a positive effect towards the development of surrounding area.